(untitled) (Research, Society and Development, 2023)
Pediatric felines are species that have anesthetic particularities, the use of opioids to control pain in pediatric anesthesia should be recommended at low doses to minimize the side effects of respiratory depression and other adverse effects generated by most of these drugs, these animals at this stage present metabolization capacity, but for safe and quality anesthesia we must also consider pre-anesthetic evaluation, clinical history, pre-operative exams, the most appropriate protocol and anesthetic monitoring. In this case report, the anesthesia of a pediatric feline that presented respiratory arrest due to the use of methadone will be discussed. A 2-month-old male feline, mixed breed, weighing 0.5 grams, underwent anesthesia at a veterinary hospital in the state of Distrito Federal for the inguinal hernia procedure. In a pre-anesthetic examination, patient ASA 3. At the end of the procedure, the animal presented mydriasis, significant respiratory depression and respiratory arrest. After the application of the total opioid reverser naloxone, the animal began to breathe again. This report aims to show the importance of using reversal drugs in anesthetic procedures in cases of adverse effects caused by the use of opioids, without ruling out further studies with the use of opioid reversals in anesthesia in felines.